2018
DOI: 10.1007/s11187-017-9979-y
|View full text |Cite
|
Sign up to set email alerts
|

Migrant entrepreneurship in China: entrepreneurial transition and firm performance

Abstract: China is experiencing rapid urbanization during which millions of migrants move from rural to urban areas. Recently, China initiated the national strategy of "mass entrepreneurship and innovation" to tap into the innovative potential and promote entrepreneurial development among the general public, with rural migrants being one of the targeted groups of this policy. This context calls for a better understanding of rural migrants' entrepreneurial formation and transition. Using the 2012 and 2014 Chinese Labor-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
1
52
0
2
Order By: Relevance
“…Existing studies have explored the entrepreneurial success of floating population through the indicator of whether there is a fixed business place , and found that local social network embeddedness is an effective way to overcome entrepreneurial difficulties and achieve entrepreneurial success. The exit rate of enterprises of floating population is even significantly lower than that of local enterprises (Liu et al, 2019).…”
Section: ) Enterprise Levelmentioning
confidence: 88%
See 4 more Smart Citations
“…Existing studies have explored the entrepreneurial success of floating population through the indicator of whether there is a fixed business place , and found that local social network embeddedness is an effective way to overcome entrepreneurial difficulties and achieve entrepreneurial success. The exit rate of enterprises of floating population is even significantly lower than that of local enterprises (Liu et al, 2019).…”
Section: ) Enterprise Levelmentioning
confidence: 88%
“…There are three main ways to measure the rural floating population: First, people with agricultural household registration who live in cities or work in cities (Liu et al, 2019;Zhang & Liu, 2014). Second, that is floating population with agricultural household registration and engaged in non-agricultural work (Jing et al, 2018).…”
Section: Definition and Measurement Of Floating Population Entreprenementioning
confidence: 99%
See 3 more Smart Citations